THE HERMENEUTICS INFLUENCE ON FEMINIST EXEGESIS: A CASE STUDY ON AMINA WADUD - Rozy, Yahya Fathur (QiST: Journal of Quran and Tafseer Studies, 2023)
This article will discuss how hermeneutic influences the exegesis of the Qur’an initiated by Muslim feminists. Through hermeneutical principles, Muslim feminists develop their own theories and methods in presenting new interpretations of the Qur'an. This research will focus its discussion on one of the well-known Muslim feminists, Amina Wadud. Through a critical study of text analysis, this research will try to answer questions about (1) the necessity of using the hermeneutical method in feminist interpretation, (2) the influence of hermeneutics on Amina Wadud's method of interpretation. This paper will highlight this event using a socio-historical approach and content analysis. In addition, references related to the patterns of Islam integrity and culture will be used with a comparative pattern. The conclusion of this research is that through historical critical analysis tools and text criticism inspired by hermeneutical principles, Amina Wadud succeeded in creating her own interpretation method and developing an interpretation approach that is not gender biased and emphasizes the principal and universal messages contained in the Qur'an.